SIDE EFFECTS OF PROTON PUMP INHIBITORS WITH LONG-TERM USE. A REVIEW OF RECENT PUBLICATIONS - Трухан, Дмитрий Иванович; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2025)
Proton pump inhibitors (PPIs) are the most effective drugs for the treatment of acid-related diseases. For a long time, PPIs were considered completely safe drugs for both short-term and long-term use. In recent years, a number of foreign reviews have been published that examine the links between long-term use of PPIs and a number of diseases/conditions, and in the domestic literature there were no reviews devoted to the safety of PPIs with their long-term use, in connection with which we conducted a search in the PubMed and Scopus information databases for publications devoted to the safety of PPI use, including sources up to 11/15/2023. Our search revealed not only an increased risk of infections and fractures due to osteoporosis, but also probable kidney pathology, possible electrolyte disturbances, the risk of cancer, cardiovascular risk and a number of rare but clinically significant side effects associated with long-term PPI therapy. In the current review, we examined publications from the PubMed and Scopus databases devoted to the safety of long-term use of PPIs for the period from 16.11.2023 to 31.12.2024. Publications of the last year confirm the association of long-term PPI therapy with an increased risk of infections, osteoporosis and associated fractures, electrolyte disturbances and kidney pathology, cancer, and CVD. In addition to those described earlier, publications of the last year discuss an increased risk of rhythm disturbances, allergies, inflammatory bowel diseases, and non-alcoholic fatty liver disease. Knowledge (and not denial) of the side effects of PPIs with their long-term use is important not only for a gastroenterologist and therapist, but taking into account the comorbidity / multimorbidity of patients and for doctors of other specialties. PPIs should be used strictly according to indications in accordance with clinical guidelines and for the shortest possible duration and at the minimum effective dose to relieve mild to moderate symptoms. Patients with clear indications (Barrett’s esophagus, erosive esophagitis C/D and a number of others in accordance with clinical guidelines) should continue long-term use of PPIs under regular control/monitoring of side effects, taking into account the patient’s comorbidity/multimorbidity.